Biondelli and the language of flowers (Atti del Sodalizio Glottologico Milanese, 2017)
In his Studii sulle lingue furbesche (1846) Bernardino Biondelli devoted some pages to “Lingua dei fiori” (flowers languages), a jargon based on rhyme, which was in use in the Ottoman Empire, during the 18th and the 19th century. This part of Biondelli’s work has been unjustly neglected. “Lingua dei fiori” shows a close similarity to the Anglo-American rhyming slang, which has been spoken in England (especially in London), at least since the 18th century, by thieves, chaunters, patterers, navvies, and which later has reached United States and Australia, where it was used by thieves, gamblers, carnies, jazzmen, students and especially in the prisons. KEYWORDS: Biondelli, jargon, language of flowers, history of linguistics, rhyming pair formations